Performance evaluation of ad-hoc on-demand distance vector protocol in highway environment in VANET with MATLAB - Osama A. Qasim; Mohammed Sami Noori; Mohand Lokman Ahmad Al Dabag (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
Vehicular ad-hoc network (VANET), the development of this network in recent years has become one of the most important areas of research. The primary goal of using the VANET network is to reduce the number of deaths and enhance road safety. VANET network faces some problems when routing packets between vehicles, due to the high-speed movement of vehicles. Therefore, researchers have begun to develop routing protocols in the VANET network to overcome these problems when routing packets between vehicles. In this study, the effect of changing the number of vehicles on the performance of ad-hoc on-demand distance vector (AODV) protocol will be studied in the highway environment and in the case of vehicle movement at variable speeds between (40-120 km/h) and the simulation time is 200 sec. The ad-hoc ondemand distance vector protocol performance was evaluated by three performance measures (end-to-end delay, dropped packets, overhead and packet delivery ratio).